EDUKASI LITERASI KEUANGAN SISWA DALAM MENGELOLA UANG SAKU (STUDI FENOMENOLOGI DI SMPN 7 KOTA JAMBI) - Muhammad Fauzi Aditya; Mayasari Mayasari; Hidayatul Arief (STKIP Pesisir Selatan, 2026)
The study aims to explore and analyze in depth the real experiences of students at SMPN 7 Jambi City in managing their daily pocket money. The study was conducted by identifying the forms of financial literacy education implemented by the school. The results obtained are an understanding of the meaning of this education for students in forming their financial habits. The novelty focuses on the depth of meaning from the perspective of key informants. A qualitative approach method with a phenomenological study design was carried out at SMPN 7 Jambi City. Data were collected from 11 participants (including the principal, vice principal, teachers, students, and parents) through observation techniques, in-depth interviews, and documentation. All data were analyzed qualitatively interactively and validated using member checking with NVivo 12 software. The results are to see the real impact of education on students' economic behavior. This was done by tracking students' responses to digital money. The phenomenon of